Diversity and Biotic Index of Wild Pioneer Plants as Potential Bioindicators of Crude Oil-Contaminated Soil in Siak Regency, Riau Province, Indonesia - Risaundi, Dodi; Suwondo, Suwondo; Arisoesilaningsih, Endang (Jurnal Pembangunan dan Alam Lestari, 2023)
This study aims to determine the spatial variations in the diversity of wild pioneer plants along the gradation of crude oil-polluted soils and to analyze their biotic potential as a bioindicator of crude oil-contaminated soils in Siak Regency. Sampling was done in three oil wells using a purposive sampling method (center, edge, far from the well) measuring 1 x 1 m2. The soil at each contamination gradation was composited and analyzed for Total Petroleum Hydrocarbon (TPH) content. Vegetation data were analyzed using biotic indices such as density, Shannon-Wiener distribution index, species richness, rate of endemism, and importance value index. Potential bioindicator was analyzed by regression analysis, biplot, and IndVal. The results showed spatial variations in colonization, diversity, and structure of pioneer plants along the gradation of oil contamination. Species from the Cyperaceae, notably Scleria sumatrensis, Cyperus rotundus, and Fimbristylis ovata, were found in the center of the contamination area and resistant to oil contamination. The regression and biplot analysis revealed that along with the increasing soil TPH, the species richness and diversity index tended to decline, but the rate of endemism increased.  IndVal analysis showed that C. rotundus and S. sumatrensis showed a potential bioindicators of oil-contaminated soils with TPH content of 2,700 to 3,300 ppm, while F. ovata, Panicum repens, and Imperata cylindrica was potential for TPH 692 to 851 ppm. Mimosa pudica was a sensitive plant and found on the soil TPH 73 ppm. Keywords:  bioindicator, crude oil-contamination,  diversity, pioneer plants